Enforcement Proceedings Under Martial Law: Problems and Ways to Solve Them - Berdar, Mykola (Problems of legality, 2025)
The purpose of the study is to analyse the legislative changes introduced in connection with martial law and assess their impact on the effectiveness of the enforcement of court decisions, as well as to identify ways to overcome the problems caused by moratoriums on collection, delays in the enforcement of court decisions, limited access to registers and difficulties in identifying debtors' property. The study was based on a comprehensive approach that combined several methods of scientific knowledge: generalization based on analysis of legislation, statistics and comparison of international experience. The study analysed the legislation of Ukraine, the USA and Germany on enforcement proceedings under martial law to identify common and distinctive features in the approaches of these countries to the regulation of enforcement proceedings under war conditions. A study of statistical data by the Ministry of Justice of Ukraine showed that the number of requests for public information to executive authorities for the period from May 2018 to 2021 increased by 170,245. Despite the fact that the number of requests for access to public information has increased, the number of open enforcement proceedings has significantly decreased, which has negatively affected the efficiency of the debt collection process. A legal analysis of foreign experience in the functioning of the system of enforcement of court decisions and decisions of other bodies has been carried out. The powers of state and private executors in the process of enforcement of decisions in countries, in particular the Federal Republic of Germany and the United States of America, have been analysed. A comparative study of enforcement proceedings in Ukraine, the USA and Germany has revealed both common features and differences in approaches to regulating this process. It has been established that all three countries recognize the need to protect the rights of debtors, especially those who have suffered from military actions or have been mobilized to defend the state. It has been revealed that Ukraine has introduced a wider list of categories of debtors subject to a moratorium on collection than the USA and Germany. The study identified the main problems of enforcement proceedings under martial law and proposed ways to solve them, in particular, improving legislation, digitalization, strengthening control, and improving the qualifications of enforcement officers.